REVOLUTIONIZING AGRICULTURE: AI-DRIVEN SMART FARMING ANALYTICS PLATFORM - Rohit Sharma (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The Smart Farming Analytics Platform represents a revolutionary advancement in agricultural technology, integrating artificial intelligence, IoT sensors, and cloud computing to transform traditional farming practices. This article presents a comprehensive analysis of the platform's implementation across 50,000 acres of diverse agro-climatic zones. The system leverages 15,000 ground-based IoT sensors, high-resolution drone imagery, and satellite data to provide real-time monitoring and actionable insights. Field trials demonstrate significant improvements in key agricultural metrics: 23% increase in crop yields, 30% reduction in water consumption, and 25% decrease in pesticide usage. The platform's AI models, combining GradientBoost and LSTM networks, achieve 92% accuracy in yield prediction, while computer vision algorithms provide real-time disease detection with up to 95% accuracy. Environmental impact analysis shows a 20% reduction in carbon footprint, 35% decrease in chemical runoff, and 15% increase in beneficial insect populations. Economic analysis reveals a 215% ROI over 24 months, with annual savings of 45,000 per 500 acres. This article demonstrates the platform's potential to revolutionize agriculture through data-driven decision-making while promoting environmental sustainability.